2015
DOI: 10.1038/srep17967
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Concentrations in Sequentially Fractionated Soil Samples as Affected by Digestion Methods

Abstract: Sequential fractionation has helped improving our understanding of the lability and bioavailability of P in soil. Nevertheless, there have been no reports on how manipulation of the different fractions prior to analyses affects the total P (TP) concentrations measured. This study investigated the effects of sample digestion, filtration, and acidification on the TP concentrations determined by ICP-OES in 20 soil samples. Total P in extracts were either determined without digestion by ICP-OES, or ICP-OES followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 36 publications
0
25
0
Order By: Relevance
“…Inorganic P (Pi) in the alkali extracts (NaHCO 3 -Pi, NaOH1-Pi, NaOH2-Pi) was determined according to Dick and Tabatabai [ 126 ] and He and Honeycut [ 127 ] to avoid overestimation of inorganic P due to mineralization of labile organic P. The method of Murphy and Riley [ 119 ] was used to determine Pi in the acid extracts (NH 4 Cl-Pi, HCl-Pi, and residual Pi). Total P (Pt) in the alkali extracts was measured using ICP-EOS according to do Nascimento et al [ 128 ], while organic P (Po) was calculated as the difference between Pt and Pi in each fraction. The total soil P was calculated as the sum of all nine fractions.…”
Section: Methodsmentioning
confidence: 99%
“…Inorganic P (Pi) in the alkali extracts (NaHCO 3 -Pi, NaOH1-Pi, NaOH2-Pi) was determined according to Dick and Tabatabai [ 126 ] and He and Honeycut [ 127 ] to avoid overestimation of inorganic P due to mineralization of labile organic P. The method of Murphy and Riley [ 119 ] was used to determine Pi in the acid extracts (NH 4 Cl-Pi, HCl-Pi, and residual Pi). Total P (Pt) in the alkali extracts was measured using ICP-EOS according to do Nascimento et al [ 128 ], while organic P (Po) was calculated as the difference between Pt and Pi in each fraction. The total soil P was calculated as the sum of all nine fractions.…”
Section: Methodsmentioning
confidence: 99%
“…The difference between TP and RP in these Mehlich‐3 extracts was NRP, which is considered here to be organic P. Digestion with alkaline persulfate was unsuccessful for these Mehlich‐3 extracts, likely due to the strong pH buffer capacity of Mehlich‐3 solution. do Nascimento et al (2015) reported that soil TP determined by inductively coupled plasma optical emission spectroscopy (ICP‐OES) may be overestimated after block digestion. Thus, we acknowledge that manipulation during digestion could introduce more variability to the final results.…”
Section: Methodsmentioning
confidence: 99%
“…Molybdate-reactive P (i. e. MRP) was measured by the molybdenum blue/ascorbic acid method4041. The TP concentration of extracts was determined after digestion with potassium persulfate (K 2 S 2 O 8 ) in an autoclave at 121 °C for 30 min42. Concentrations of P o in extracts were then calculated as the difference between concentrations of TP and MRP.…”
Section: Methodsmentioning
confidence: 99%